2011
DOI: 10.1287/mnsc.1100.1247
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Spaces in Innovation: Empirical Analysis of Large Samples of Ideas

Abstract: A common approach to innovation, parallel search, is to identify a large number of opportunities and then to select a subset for further development, with just a few coming to fruition. One potential weakness with parallel search is that it permits repetition. The same, or a similar, idea might be generated multiple times, because parallel exploration processes typically operate without information about the ideas that have already been identified. In this paper we analyze repetition in five data sets comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 54 publications
1
107
0
2
Order By: Relevance
“…Information jams encourage employees to post suggestions to a shared bulletin board and then vote good ideas up or down (although most systems do not blind the voter to the ratings of other participants, opening the door for influence). Kornish & Ulrich (2011) looked at the effectiveness of idea jams by having different populations generate new possible products for a given setting (e.g., for the web or for the classroom). Ideas were then provided to a different sample of participants to rate for quality.…”
Section: The Wisdom Of Crowdsmentioning
confidence: 99%
“…Information jams encourage employees to post suggestions to a shared bulletin board and then vote good ideas up or down (although most systems do not blind the voter to the ratings of other participants, opening the door for influence). Kornish & Ulrich (2011) looked at the effectiveness of idea jams by having different populations generate new possible products for a given setting (e.g., for the web or for the classroom). Ideas were then provided to a different sample of participants to rate for quality.…”
Section: The Wisdom Of Crowdsmentioning
confidence: 99%
“…The assumption is that a good solution is more likely to emerge from many solvers than an individual solver. Some scholars argue that problem solving through innovation contests may generate similar or redundant solutions (Girotra et al, 2010), but others argue that, even though there might be a redundancy of solutions in parallel settings, it is insignificant even in a very narrow area (Kornish & Ulrich, 2011). Another example of a problem-solving platform is OpenIDEO (openideo.com), a global community used by many organizations to solve world's pressing problems.…”
Section: Problem-solving Platformsmentioning
confidence: 99%
“…Kornish & Ulrich (2011) have studied the effectiveness of parallel efforts to the generation of ideas. They found through the study of a set of data that: although there is redundancy of ideas due to parallel efforts, it is small; and ideas which have a redundancy tend to be most valuable.…”
Section: Outcome Of the Idea Management Processmentioning
confidence: 99%
“…The authors concluded that there is a greater need for research to better understand the product concept phase. The works from Blau & McKinley (1979) and Kornish & Ulrich (2011) follow a similar path, since they studied the impact of ideas on organizational results.…”
Section: Outcome Of the Idea Management Processmentioning
confidence: 99%